The relationship between outpatient service use and emergency department visits among people treated for mental and substance use disorders: analysis of population-based administrative data in British Columbia, Canada - M. Ruth Lavergne; Jackson P. Loyal; Mehdi Shirmaleki; Ridhwana Kaoser; Tonia Nicholls; Christian G. Schütz; Adam Vaughan; Hasina Samji; Joseph H. Puyat; Megan Kaulius; Wayne Jones; William Small (BMC Health Services Research, 2022)
Abstract Background Research findings on the association between outpatient service use and emergency department (ED) visits for mental and substance use disorders (MSUDs) are mixed and may differ by disorder type. Methods We used population-based linked administrative data in British Columbia, Canada to examine associations between outpatient primary care and psychiatry service use and ED visits among people ages 15 and older, comparing across people treated for three disorder categories: common mental disorders (MDs) (depressive, anxiety, and/or post-traumatic stress disorders), serious MDs (schizophrenia spectrum and/or bipolar disorders), and substance use disorders (SUDs) in 2016/7. We used hurdle models to examine the association between outpatient service use and odds of any ED visit for MSUDs as well count of ED visits for MSUDs, stratified by cohort in 2017/8. Results Having had one or more MSUD-related primary care visit was associated with lower odds of any ED visit among people treated for common MDs and SUDs but not people treated for serious MDs. Continuity of primary care was associated with slightly lower ED use in all cohorts. One or more outpatient psychiatrist visits was associated with lower odds of ED visits among people treated for serious MDs and SUDs, but not among people with common MDs. Conclusion Findings highlight the importance of expanded access to outpatient specialist mental health services, particularly for people with serious MDs and SUDs, and collaborative models that can support primary care providers treating people with MSUDs.